Plataforma para auxiliar na identificação do mecanismo de ação de herbicidas para pastagens em Rondônia - (:unkn) unknown (Universidade Brasil, 2024)
In the state of Rondônia, livestock production is based on the implementation of grasses in cultivated pasture areas, both for beef and dairy cattle farming, in an extensive system. Weed interference is one of the factors that most affect the productivity of annual and perennial crops in Brazil. Faced with so many challenges faced by the agricultural sector, the recognition of the main invasive plants and their control are essential for decision-making on the application of herbicides to pastures, in order to avoid greater economic losses, damage to the environment and the user's health. Knowledge of the mechanism of action of groups of herbicides can provide fundamental information when choosing and rotating the mechanism of action of herbicides is important for preventing the development of resistant biotypes and for the environment. The objective of this work was to develop a platform with the aim of assisting in the identification of weeds in pastures and assisting in the indication of herbicides based on their mechanism of action, in the state of Rondônia. To this end, a total of 234,345 agronomic prescriptions with diagnosis for controlling weeds in pasture were tabulated. The data was collected from Power BI, a government program in the Computerized Control System for Pesticides Trade Inspection - SIAFRO. From this, a spreadsheet was generated with the identification of the main infesting weeds, chemical control and mechanism of action, with the quantity of each weed and its control. This data served as a database to supply the developed platform. The platform was developed using a combination of WEB languages, namely html, Javascript, php and mysql database. The developed platform was named SIHPASTO and can be accessed through the link www.pmppa.com.br/herbicida. It is concluded that the platform helped to identify the most common weeds in the State of Rondônia and to indicate herbicides with different mechanisms of action.
Keywords: Mecanismo de ação; Pastagem; Plantas daninhas; Zootecnia de precisão; Produção Animal